The Effectiveness of Acceptance and Commitment Therapy on Depression, Anxiety, and Quality of Life in Men with Asthma - Moeinoddini, Roya; Rafiepoor, Amin; Kordmirza Nikoozadeh, Ezzatollah (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The aim of this research was to investigate the effectiveness of Acceptance and Commitment Therapy (ACT) in reducing depression, anxiety, and improving the quality of life in men with asthma. Methods and Materials: This study was quasi-experimental with a pretest-posttest design and a control group. The sample consisted of 30 men with asthma who were randomly assigned into two groups of 15: the intervention group, which received Acceptance and Commitment Therapy, and the control group, which did not receive any intervention. The research instruments included the Beck Depression Inventory-II (BDI-II), State-Trait Anxiety Inventory (STAI), and Asthma Quality of Life Questionnaire (AQLQ). Findings: The results showed that Acceptance and Commitment Therapy significantly reduced depression and anxiety and improved the quality of life in the intervention group compared to the control group. Conclusion: These findings indicate the efficacy of this therapy in improving the psychological state and quality of life in patients with asthma.